Bildung na contemporaneidade : alguns legados pedagógicos de Goethe - Marangon, Marcio Luis (2013)
The present work tries to problematize current state of education an enlarged conception of education, having as reference the work Os Anos de Aprendizagem de Wilhelm Meister , of Goethe. The guiding hypothesis of the investigation is based on the idea that the proposal of formation developed by Goethe in the mentioned work can contributed to the problematization of the current education and present indications to a revision of concept in formation. It is a reconstructive analytical work in which, after a brief diagnosis on current education, one tries to rebuilt some of the main ideas in formation that are seen in the original work and that can be productive for the critical development of current education: subjectivity, self cultivation, perfectability and universality. This dissertation is organized in three chapters: the first one brings an analysis of some aspects of contemporary society which contribute to the crisis in current education. The second chapter presents a brief rescue g of the fundamental conceptions about Bildung his thinkers, his currents, his influences and main pedagogical conceptions and, more detailed, an analyses of Goethe: Os anos de aprendizagem de Wilhelm Meister . The third chapter makes a resumption of the formation concept from the character Wilhelm Meister and makes some analytical confronts aiming at possible alternatives to the human formation in contemporary society enlightened by Goethe s pedagogical view. At last, the text forwards some important appointments giving emphasis to the importance of the resumption of some concepts of formations forged by Bildung and, especially by Goethe, for the reestablishment caption of an enlarged and critical conception of education